Improving the Learning Outcomes of Students in Fiqh Subject Class V through the Mind Mapping Method at Madrasah Ibtidaiyah Nurus Salam Palengaan Laok Palengaan Pamekasan - Fadilah, Fadilah (LP2M IAI Al-Khairat Pamekasan, 2024)
There are three problems that are the focus of this research, namely how to apply the mind mapping method to fifth grade fiqh subjects at Madrasah Ibtidaiyah Nurus ‎Salam Palengaan Laok Palengaan Pamekasan? How to increase student learning outcomes after applying the mind mapping method to class V fiqh subjects at Madrasah Ibtidaiyah Nurus Salam Palengaan Laok Palengaan Pamekasan? What are the supporting and inhibiting factors for the application of the mind mapping method in improving student learning outcomes in fiqh class V at Madrasah Ibtidaiyah Nurus ‎Salam Palengaan Laok Palengaan Pamekasan? This research is a type of descriptive research using a qualitative approach. The data sources are ustadz/teachers and students of Madrasah Ibtidaiyah Nurus Salam. Data was collected through interviews, observations, and documentation. Then analyzed with descriptive-qualitative analysis.